IMPLEMENTASI KOMPETENSI ALUMNI PRODI TEKNOLOGI PENDIDIKAN UNIVERSITAS NEGERI PADANG SEBAGAI PENGEMBANG TEKNOLOGI PEMBELAJARAN - Richi Gusti Amelia (E-Tech : Jurnal Ilmiah Teknologi Pendidikan, 2021)
Alumni Program FIP TP UNP, have the competence as a Developer LearningTechnology. Developer Learning Technology is a profession that finds a wayout in the form of design, development, utilization, pengelolaaan, assessmentand research to overcome learning problems either individuals or groups.This study aims to determine the competence implementation alumni ofEducational Technology Faculty of Education, University of Padang (1) theactivities carried out, (2) problems faced (3) attempts to overcome theproblems.This study used descriptive qualitative approach. The main subjectof this research is the alumni TP FIP UNP, while supporting a subject thatsuperiors and colleagues alumni of TP FIP UNP. Data collection techniqueusing interviews, observation, and documentation. Data analysis techniqueInteraktive models used by Milles and Huberman (Sugiyono, 2018) byreduction of the data (data reduction), presentation of data (data display),and conclusion (Conclusions verivication).The validity of the data obtainedthrough triangulation, triangulation techniques, and triangulation of time.The results showed (1) Alumni TP FIP UNP TP functional competence inimplementing PTP activity analysis and assessment, design, development,implementation, and evaluation of system / learning models, while the alumniTP FIP UNP Non PTP implement appropriate competence TP job field. (2)The problem faced by the unavailability TP formation instituted education(elementary, secondary, vocational) as PTP, Competence alumni of TP arestill little known in the community (3) efforts to overcome the problems is toincrease the competence of alumni, participated in the training, adaptation ofthe work environment, and actively in activities that increase competency.